Muscle coactivation during stability exercises in rhythmic gymnastics: A two-case study - Rutkowska-Kucharska, A.; Szpala, A.; Jaroszczuk, S.; Sobera, M. (Applied Bionics and Biomechanics, 2018)
Balance exercises in rhythmic gymnastics are performed on tiptoes, which causes overload of foot joints. This study aimed to evaluate the engagement of muscles stabilizing ankle and knee joints in balance exercises and determine exercises which may lead to ankle and knee joint injuries. It was hypothesized that long-term training has an influence on balance control and efficient use of muscles in their stabilizing function. Two rhythmic gymnasts (8 and 21 years old) performed balances on tiptoes (side split with hand support, ring with hand support) and on a flat foot (back split without hand support exercise). Surface electromyography, ground reaction forces, and kinematic parameters of movement were measured. The measuring systems applied were synchronized with the BTS SMART system. The results show the necessity to limit balance exercises on tiptoes in children because gastrocnemius medialis (GM) and gastrocnemius lateralis (GL) activity significantly exceeds their activity. Ankle joint stabilizing activity of GM and GL muscles in the younger gymnast was more important than in the older one. Performing this exercise, the younger gymnast distributed load on the anterior side of the foot while the older one did so on its posterior. Gymnastics coaches should be advised to exclude ring with hand support exercise from the training of young gymnasts.